Procalcitonin Uptake and Effect on Antibiotics Stewardship: A Single Institution Experience - Ahaneku, MD DrPH, Hycienth; Umeh, MD DrPH, Chukwuemeka A.; Cao, MD, Mike; Kapten, MD, Bradley; Elhalwagi, MD, Baher; Egbe, MD, Tiffany; Elueze, MD, PhD, Emmanuel (International Journal of Innovative Research in Medical Science, 2020)
Background: In the face of antibiotics resistance and adverse effects, emerging evidence suggests that procalcitonin guided therapy can help enhance appropriate use of antibiotics especially in patients with respiratory infections and sepsis. We seek to assess the uptake of procalcitonin among clinicians in a US hospital and assess its correlation with amount and duration of antibiotics use. We also seek to identify factors significantly associated with antibiotic use. Methodology: Retrospective cross-sectional study of patients with sepsis and COPD at a Medical Center in Texas USA. A total 48 COPD and 62 Sepsis patients were assessed. We collected demographic data such as age, weight, height, gender, and race/ethnicity. We also collected data on procalcitonin, number of antibiotics used, duration of antibiotics, and WBC levels at admission. We conducted bivariate analyses and logistic regression analyses to assess factor associated with procalcitonin, number of antibiotics used and duration of antibiotics. Results: We had 48 COPD patients and 62 sepsis patients in this study. Overall physicians ordered Procalcitonin on only 11.8% of patients. Procalcitonin was not significantly associated with antibiotics use. However, patients who had procalcitonin ordered had significantly lower WBC count than those without procalcitonin (10.1 vs. 12.9, p:0.026). Number of antibiotics was significantly associated with type of diagnosis (Sepsis 66.7% vs. COPD 50.7%, p = 0.001). In the logistic regression analysis, after adjusting for other variables patients with sepsis were significantly more likely to be on higher number antibiotics (OR 6.08, p <0.001) and longer duration of antibiotics (OR 7.44, p < 0.001). Conclusion: Inappropriate use of antibiotics is a public health problem. Procalcitonin has been touted as a biomarker that is effective in reducing use of antibiotics. Our study showed a low utilization of Procalcitonin by physicians and that patients with lower WBC counts were more likely to have procalcitonin ordered. However, our study did not find any association between procalcitonin and the number and duration of antibiotics use.